Nomenclatural notes on Cruciferae - Дмитрий Александрович Герман (Turczaninowia, 2019)
A generic name Dvorakia and combinations Arabidopsis amurensis, A. media, A. multijuga, A. septentrionalis, Dvorakia alaica, D. alyssifolia, Erophila acutidentata, E. aquisgranensis, E. kohlscheidensis, and E. strigosula are validated. Places of valid publication and (except for the first combination) authorship for Erysimum krynitzkii, Eunomia bourgaei, E. rubescens, Pseudocamelina aphragmodes, P. campylopoda, and Thlaspi hastulatum are corrected. For Pseudocamelina and Peltariopsis, information on the types is clarified. Some further minor nomenclatural items are commented.